1997
DOI: 10.1093/jac/39.3.393
|View full text |Cite
|
Sign up to set email alerts
|

Two-year-outcomes analysis of Crohn's disease treated with rifabutin and macrolide antibiotics

Abstract: Fifty-two patients with severe Crohn's disease were enrolled in this study. Six (11.5%) were intolerant of the medication and had to be excluded. The remaining 46 patients were treated with rifabutin in combination with a macrolide antibiotic (clarithromycin or azithromycin). Patients were treated for a mean of 18.7 (range 6-35) months and followed up for 25.1 (range 7-41) months. Of the 19 patients who were steroid dependent at the start of this study, only two continued to require steroids when treatment was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(67 citation statements)
references
References 39 publications
2
59
0
4
Order By: Relevance
“…Mucosal homeostasis is intricately linked with the community of microbial residents of the gut, the so-called gut microbiota. Both animal (22,33,42) and clinical (11,14,39) studies support the view that changes in the density and composition of the intestinal microbiota (dysbiosis) lead to initiation and perpetuation of IBD, although it is not known whether this imbalance is driven by functional alteration of the commensal gut microbial population or introduction of pathogenic species.…”
Section: Inflammatory Bowel Disease (Ibd) Is An Umbrella Term For a Gmentioning
confidence: 98%
“…Mucosal homeostasis is intricately linked with the community of microbial residents of the gut, the so-called gut microbiota. Both animal (22,33,42) and clinical (11,14,39) studies support the view that changes in the density and composition of the intestinal microbiota (dysbiosis) lead to initiation and perpetuation of IBD, although it is not known whether this imbalance is driven by functional alteration of the commensal gut microbial population or introduction of pathogenic species.…”
Section: Inflammatory Bowel Disease (Ibd) Is An Umbrella Term For a Gmentioning
confidence: 98%
“…The authors who favor MAP as causative agent remark that most IBD antibiotic regimens are not fully effective for MAP and that good MAP treatments need to include macrolides, should include triple or quadruple therapies, or should be sustained for very long periods of time, as is done in tuberculosis treatment. Several long-term regimens have been performed, showing initial improvement, with steroid weaning, but concluding that the benefit is not sustained [58,59] . A two-year combination antibiotic therapy with clarithromycin, rifabutin, and clofazimine for CD was used in a study performed in Australia, in which significant improvement up to week 16 was observed, although subsequent follow-up results were not conclusive.…”
Section: Mycobacterium Avium Paratuberculosismentioning
confidence: 99%
“…In CD, Mycobacterium avium subspecies paratuberculosis (MAP) is a recurrent candidate for several reasons: its association with epidemic bovine colitis, the presence of anti-MAP antibodies and MAP sequence by polymerase chain reaction (PCR) CD patients, and some reports that antimycobacterial drugs ameliorate disease (143)(144)(145)(146). However, other groups were unable to detect these microorganisms, and the prevalence of disease-associated anti-MAP antibodies is variable.…”
Section: Candidate Microbial Pathogens and Mucosal Dysbiosismentioning
confidence: 99%